Crimes sexuais no sudeste do Paraná : as contravenções morais dos migrantes na comarca de Clevelândia (1953-1979) - Sumocoski, Denilson (2012)
The Southwest region of Paraná should be understood as a concern of the Brazilian state since the imperial period, when there were colonies of military installations and Chapecó Chopim. This phenomenon was repeated when they were created in the mid-twentieth century, agricultural colonies and the main exponent of the CANGO (National Agricultural Colony General Osório), whose specific function, settlement and protection of the border area with Argentina. In that period that corresponded to the beginning of the 30s, Brazil was led by Vargas, and even extends to the occupation of the Southwest region with the policy called "March to the West". Relevant to note that the Southwest region had its geographical space occupied with greater intensity after the first decades of the last century, that because the displacement of European immigrants who had occupied the Serra Gaucha and were thus displaced in a process of internal migration to Southwest Parana. However it is not correct to say that the region before it, was a huge demographic void as traditional historiography between the decades of 70-80 report. Migrants and their descendants, who occupied the region, are the direct protagonists of this research, since the analyzes of sex crimes occur around this group. Crimes of rape and defloration were analyzed as reference entity, the penal code of 1940. The research aims to analyze the contradictions between the official discourse moralizing proclaimed by the Catholic Church and the State, and, as a counterpoint, the processes of sex crimes committed in the region between the years 1953-1979. The largest analysis of the background is to understand the contradiction between the idealized profile government forces and religious practices not consistent and proven by the existence of processes that crimes denounced the actions judicially and morally disapproved by local society.